School Scoliosis Screenings: Family Experiences and Potential Anxiety After Orthopaedic Referral. Issue 21 (November 2015) - Hines, Tabatha; Roland, Sandy; Nguyen, Dylan; Kennard, Beth; Richard, Heather; Hughes, Carroll W.; McClintock, Shawn M.; Ramo, Brandon; Herring, Tony
Abstract : Study Design: Cross-sequential study design that used data from Texas Scottish Rite Hospital for Children (TSRHC). Objective: Examine anxiety symptoms and family experiences subsequent to school scoliosis screening (SSS) referrals. Summary of Background Data: Use of SSS remains controversial. Prior research suggested that SSS programs may result in anxiety for both children and parents. Unfortunately, no study has examined the SSS referral processes and anxiety in families. Methods: Study consisted of 2 groups—patients/parents from TSRHC evaluated for Adolescent Idiopathic Scoliosis (AIS) (n = 27) and control participants/parents (n = 27) between ages 9 and 17. All participants completed the primary outcome measure (State-Trait Anxiety Inventory) before and after the scoliosis evaluation or controlled wait time. Parents also rated experience and satisfaction with SSS. Results: Compared with the control group, children/parents in patient group experienced significantly elevated levels of state-anxiety at preappointment. Children/parents in the patient group not diagnosed with AIS experienced a significant decline in state-anxiety. Children/parents in the patient group diagnosed with AIS continued to report elevated levels of anxiety. The control group remained consistent, reporting of low levels of anxiety pre to post. More than half (55.5%) of families indicated they received no information from the school about scoliosis. A third of the families who received information indicated it did not adequately address their concerns. Nonetheless, most families reported overall satisfaction with SSS. Conclusion: This study suggested that children and parents referred through the SSS program experienced significantly elevated levels of state-anxiety. This supports the subjective concerns of anxiety experiences in families voiced by researchers previously. However, families deemed the costs of the SSS referral process as worth the benefits. Though challengers of SSS programs were accurate in observing anxiety in families, it may not constitute significant burden to eliminate SSS programs altogether. Improvements to the current system may be warranted. Level of Evidence: 3